Pulse electrodeposition of Nd-doped SnO2-based electrocatalysts for enhanced electrochemical production of ozone and active chlorine - Fuchang Duan; Jinglei Si; Xiaoge Peng; Xiaosa Wang; Yang Ding; Wei Guo; Pan Hu; Yanan Deng; Haibo Lin; Haoqiang Cao; Yunyi Cao; Xing Zhong; et al. (Chemical Engineering Journal, 2026)

The influence of pulsed electric fields with different waveforms on the extraction of valuable compounds from microalgae - Liuxia Li; Yifan Gao; Zihuang Peng; Xun Pei; Ruorong Hua; Fuchang Lin; Rui Zhang; Yi Liu (Innovative Food Science & Emerging Technologies, 2025)

Influence of Electrode Size on the Fragmentation Process of Rocks with Different Heterogeneities under High-Voltage Pulses - Yong Zhao; Yi Liu; Hongbin Liao; Tianyu Wang; Siwei Liu; Fuchang Lin (Rock Mechanics and Rock Engineering, 2025)

Electroporation of Chlorella vulgaris with laboratory devices capable of generating arbitrary waveform pulses - Liuxia Li; Zihuang Peng; Nan Liu; Yi Liu; Hua Li; Qin Zhang; Fuchang Lin (Innovative Food Science & Emerging Technologies, 2024)

Contribution of SST change to multidecadal global and continental surface air temperature trends between 1910 and 2013 - Yidan Xu; Jianping Li; Cheng Sun; Xiaopei Lin; Hailong Liu; Lanning Wang; Yishuang Liang; Qiuyun Wang; Yazhou Zhang; Zhaolu Hou; Fuchang Wang (Climate Dynamics, 2020)
The global mean surface air temperature (GMST) shows multidecadal variability over the period of 1910–2013, with an increasing trend. This study quantifies the contribution of hemispheric surface air temperature (SAT) variations and individual ocean sea surface temperature (SST) changes to the GMST multidecadal variability for 1910–2013. At the hemispheric scale, both the Goddard Institute for Space Studies (GISS) observations and the Community Earth System Model (CESM) Community Atmosphere Model 5.3 (CAM5.3) simulation indicate that the Northern Hemisphere (NH) favors the GMST multidecadal trend during periods of accelerated warming (1910–1945, 1975–1998) and cooling (1940–1975, 2001–2013), whereas the Southern Hemisphere (SH) slows the intensity of both warming and cooling processes. The contribution of the NH SAT variation to the GMST multidecadal trend is higher than that of the SH. We conduct six experiments with different ocean SST forcing, and find that all the oceans make positive contributions to the GMST multidecadal trend during rapid warming periods. However, only the Indian, North Atlantic, and western Pacific oceans make positive contributions to the GMST multidecadal trend between 1940 and 1975, whereas only the tropical Pacific and the North Pacific SSTs contribute to the GMST multidecadal trend between 2001 and 2013. The North Atlantic and western Pacific oceans have important impacts on modulating the GMST multidecadal trend across the entire 20th century. Each ocean makes different contributions to the SAT multidecadal trend of different continents during different periods.

A coupled experiment with LICOM2 as the ocean component of CESM1 - Pengfei Lin; Hailong Liu; Wei Xue; Huimin Li; Jinrong Jiang; Mirong Song; Yi Song; Fuchang Wang; Minghua Zhang (Journal of Meteorological Research, 2016)